The impact of leadership style and work environment on employee performance at PT Mentari Anugerah Prima West Jakarta - Ana Septia Rahman (Jurnal Mantik, 2024)
The objective of this study was to ascertain the extent to which leadership style and work environment impact employee performance at PT Mentari Anugerah Prima, located in West Jakarta. This study employs quantitative research methodologies with an associative quantitative approach. The population comprises all the employees in the PT, amounting to a total of 65 individuals. The specimen was collected employing a saturation sampling methodology, wherein the complete populace of 65 individuals was utilised as a sample. The data analysis employed in this study includes validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The findings indicate that there is a correlation between leadership style and employee performance, as seen by the t-test results with a t count of 8.245, which is greater than the t table value of 1.670. Therefore, Ha1 is accepted and Ho1 is rejected, suggesting that leadership style has a partial impact on employee performance. The outcomes of the t-test for the work environment, with a t-count of 12.128 and a t-table of 1.670, lead to the acceptance of Ha2 and the rejection of Ho2. This implies that the work environment has a partial impact on employee performance. Although the f test findings indicate that the value of fcount 81.829 is greater than ftable 3.145, this implies that both leadership style and work environment have a notable impact on employee performance.